RISK ANALYSIS OF AGRO-INDUSTRIAL WASTES GASIFICATION IN FLUIDIZED BED - Muñoz, Moisés; Palacios, Carlos; Echegaray, Marcelo; Rodriguez, Rosa (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
Thermochemical conversion processes used to convert agro-industrial wastes are increasingly common, for economic and environmental reasons. Due to CO2 accumulation in the atmosphere, biomass wastes gasification has the potential to significantly contribute to more environmentally friendly energy services. Fluidized bed reactor is currently one of the most promising technologies of energy conversion because its advantages. However, the challenges and approaches of the safety and risk management for the syngas production using the fluidized bed reactor have been far from sufficiently examined. This work presents the identification of different risk using the MAD-MOSAR method, recognizing the short and long scenarios. Different risk hazards for the biomass gasification in fluidized bed reactor were evaluated using the Life Cycle Risk Assessment. The most important subsystems involved in the long scenario of damage and injury are supply of natural gas and compressed air and/or steam, fluidized bed reactor gasifier, syngas cooling and cleaning systems and gas engine generator.